Ovarian Biomechanics: From Health to Disease - Sun, Chenchen; Yang, Xiaoxu; Wang, Tianxiao; Cheng, Min; Han, Yangyang (Frontiers in Oncology, 2022)
Biomechanics is a physical phenomenon which mainly related with deformation and movement of life forms. As a mechanical signal, it participates in the growth and development of many tissues and organs, including ovary. Mechanical signals not only participate in multiple processes in the ovary but also play a critical role in ovarian growth and normal physiological functions. Additionally, the involvement of mechanical signals has been found in ovarian cancer and other ovarian diseases, prompting us to focus on the roles of mechanical signals in the process of ovarian health to disease. This review mainly discusses the effects and signal transduction of biomechanics (including elastic force, shear force, compressive stress and tensile stress) in ovarian development as a regulatory signal, as well as in the pathological process of normal ovarian diseases and cancer. This review also aims to provide new research ideas for the further research and treatment of ovarian-related diseases.